Pan-African is Pan-Gondwanaland:Oblique convergence drives rotation during 650-500 Ma assembly - Veevers, JJ (2003)
Gondwanaland was assembled by 650-570 Ma oblique subduction of ocean floor between cratons, including the Mozambique Ocean between West and East Gondwanaland. Oblique convergence set the cratons into a series of counterrotating cogs that sheared the intervening fold belts. The 550-490 Ma oblique subduction of paleo-Pacific ocean floor beneath Antarctica extended the system of counterrotating cogs and shear deformation to the Transantarctic Mountains and northern Australia. Terminal subduction was followed by epeirogenic uplift and concomitant stripping indicated by ubiquitous ca. 500 Ma K-Ar and apatite fission-track dates. These deep-seated events, recorded by zircons of 650-500 Ma age, and first noted in Africa ("Pan-African"), are now recognized as "Pan-Gondwanaland."